2009
DOI: 10.1017/s1463423609990156
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with access to healthcare: qualitative study of rural patients and practitioners

Abstract: Aim: To gain insight into factors affecting patient and practitioner satisfaction with access to healthcare in a remote rural island community. Background: General practice based primary care is the focus of health service delivery in rural areas of the UK. Individuals from rural populations have reported inequalities in access to healthcare. User satisfaction with service performance is recognised as an important outcome of healthcare. Further investigation into factors underpinning patient and practitioner s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…patient satisfaction, management of diabetes and hyperlipidemia) associated with practices that included non-physicians such as nurses and physician assistants [31,32]. A recent study using UK general practice data also indicated that team-based practice is associated with better processes of care for patients with diabetes, improved continuity of care, access to care, and patient satisfaction [14]. Studies based on Australian data found evidence of improved diabetes control in patients who were treated by a multidisciplinary team and had a pre-care plan for managing their HbA1c levels [33].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…patient satisfaction, management of diabetes and hyperlipidemia) associated with practices that included non-physicians such as nurses and physician assistants [31,32]. A recent study using UK general practice data also indicated that team-based practice is associated with better processes of care for patients with diabetes, improved continuity of care, access to care, and patient satisfaction [14]. Studies based on Australian data found evidence of improved diabetes control in patients who were treated by a multidisciplinary team and had a pre-care plan for managing their HbA1c levels [33].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies suggest that teambased practice is positively associated with improved patient outcomes, such as increased access, improved quality of service, effective management of chronic diseases [3,5,[11][12][13][14][15][16][17]. By contrast, other studies suggest a negligible impact of team-based PHC delivery on patient outcomes: limited access to physicians, compromised continuity of care, duplication of efforts, creation of barriers of disciplinary territoriality, systems inertia and organizational complexity [11,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Local professionals and politicians must take into account that the conditions of rural geography create different health care needs when planning for rural citizens [1]. People in rural areas do not have access to the same range of services as those in urban areas [2].…”
Section: Introductionmentioning
confidence: 99%
“…When someone is dying, the whole community knows. Patients may not divulge personal information for fear of loss of anonymity, but are conversely more trusting of the health care staff because they know them . Equally there is a level of professional risk for health professionals and volunteers if patients or caregivers become disenfranchised with the care they receive …”
Section: Psychosocial Impact Of End Of Life Care In Rural Communitiesmentioning
confidence: 99%